2012
DOI: 10.1155/2012/278652
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxicity Mechanism of 6-Shogaol-Treated HeLa Human Cervical Cancer Cells Revealed by Label-Free Shotgun Proteomics and Bioinformatics Analysis

Abstract: Cervical cancer is one of the most common cancers among women in the world. 6-Shogaol is a natural compound isolated from the rhizome of ginger (Zingiber officinale). In this paper, we demonstrated that 6-shogaol induced apoptosis and G2/M phase arrest in human cervical cancer HeLa cells. Endoplasmic reticulum stress and mitochondrial pathway were involved in 6-shogaol-mediated apoptosis. Proteomic analysis based on label-free strategy by liquid chromatography chip quadrupole time-of-flight mass spectrometry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…of human cancer cell lines in vitro (6)(7)(8). Previous studies have demonstrated that 6-shogaol induced apoptosis of hepatocellular carcinoma and cervical cancer via endoplasmic reticulum stress (9,10). Additionally, increasing evidences have demonstrated that this plant polyphenol is a potent blocker of the NF-κB pathway (6,11,12).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…of human cancer cell lines in vitro (6)(7)(8). Previous studies have demonstrated that 6-shogaol induced apoptosis of hepatocellular carcinoma and cervical cancer via endoplasmic reticulum stress (9,10). Additionally, increasing evidences have demonstrated that this plant polyphenol is a potent blocker of the NF-κB pathway (6,11,12).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Studies have previously shown that 6-Shogaol has anti-proliferative, anti-survival, and pro-apoptotic effects on many different types of human cancer cells, such as SMMC-7721 (liver), HGC (gastric), A2780 (ovarian), COLO 205 (colon), A549 (lung), HeLa (cervix), and MDA-MB-231 (breast) [ 30 , 31 , 32 , 39 , 41 , 42 , 43 ]. The known molecular mechanisms underlying 6-Shogaol’s anticancer effects include the induction of apoptosis, the activation of caspase-9, -8, -3, the accumulation of sub G1 phase cells [ 30 , 42 , 43 , 44 , 45 , 46 ], and the arrest of the cell cycle [ 47 ]. Through initial experiments, we herein have demonstrated that 6-Shogaol at 20 μM largely reduces the survival of SW872 and 93T449 human liposarcoma cells, but it does not affect normal 3T3-L1 preadipocytes, suggesting the specificity of 6-Shogaol to inhibit adipocytic tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of various natural dietary agents, especially spices and herbs, in health promotion, including the suppression of cancer, have attracted considerable attention (16). Liu et al (17) reported that 6-shogaol, a natural compound isolated from the rhizome of ginger, induced apoptosis and G 2 /M-phase cell-cycle arrest in human cervical cancer (HeLa) cells. In a proteomic analysis, they found that the peak intensities of 76 proteins in HeLa cells changed (54 upregulated and 22 downregulated) by more than two-fold after treatment for 24 h with 15 μM 6-shogaol, relative to their levels in vehicle-treated cells.…”
Section: Roles Of 14-3-3 Proteins In the Treatment Of Cervical Cancermentioning
confidence: 99%